2008
DOI: 10.1021/tx800152r
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Nimesulide Studies toward Understanding Idiosyncratic Hepatotoxicity: Diiminoquinone Formation and Conjugation

Abstract: Nimesulide is a nonsteroidal anti-inflammatory drug (NSAID) marketed in more than 50 countries. This drug has caused rare and idiosyncratic but severe hepatotoxicity. The mechanisms associated with and factors responsible for this toxicity remain unknown. One of the nimesulide metabolites identified in human urine is 4-amino-2-phenoxy-methanesulfonanilide (M1). In the current study, we demonstrate that M1 is a stable metabolite that is highly susceptible to facile oxidation by cytochrome P450 enzymes (P450s) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 26 publications
3
35
0
Order By: Relevance
“…67 In addition, NiNH 2 can completely suppress the uncoupling and NAD(P)H oxidant effects on mitochondria. 68,69 In this study, the nitro group of nimesulide was reduced to amine first and then grafted onto HA, suggesting that HA-nimesulide might reduce the liver toxicity effects of free nimesulide.…”
Section: Cell Growth Inhibition By Ha-nimesulidementioning
confidence: 81%
“…67 In addition, NiNH 2 can completely suppress the uncoupling and NAD(P)H oxidant effects on mitochondria. 68,69 In this study, the nitro group of nimesulide was reduced to amine first and then grafted onto HA, suggesting that HA-nimesulide might reduce the liver toxicity effects of free nimesulide.…”
Section: Cell Growth Inhibition By Ha-nimesulidementioning
confidence: 81%
“…Bottom, a remoxipride metabolite (MQS: 0.58), 108 thioridazine (MQS 0.36), 101 and a flutamide metabolite (MQS 0.88). 109 The atoms of experimentally observed quinone forming pairs are circled. Scores (ranging from 0 to 0.99) are indicated by colored shading, assigning each atom the probabilistic OR of all pair-level quinone formation scores including the atom.…”
Section: Figurementioning
confidence: 99%
“…The EMA has concluded that the benefits of these medicines outweigh their risks, but that there is a need to limit the duration of use to ensure that the risk of patients developing liver problems is kept to a minimum. Therefore the EMA has limited the use of systemic formulations (tablets, solutions, suppositories) of NIM-containing medicinal products to 15 days because of reports of severe hepatic adverse reactions (EMA, 2007;Li et al, 2009). …”
Section: These Cases Occurred In the Period From 1999 To 2006 (Imb 2mentioning
confidence: 99%